2021
DOI: 10.3390/ani11020477
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Serum Protein Electrophoretic Pattern and Leukocyte Population in Horses Vaccinated against West Nile Virus

Abstract: This study aimed to evaluate the hematological and serum protein electrophoretic profiles of horses after inactivated West Nile virus (WNV) vaccine administration. Blood samples were collected from 10 horses before (T0), after 24 h, 48 h, 72 h, 1 week, 2 weeks and 3 weeks (T1I, T2I, T3I, T4I, T5I and T6I) from the first WNV vaccine-dose administration, before the vaccine-booster (TPREII), and after 24 h, 48 h, 72 h, 1 week, 2 weeks and 3 weeks (T1I I, T2II, T3II, T4II, T5II, T6II) from the WNV vaccine-booster.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This highlights that adapting protocols based on titers can be achieved for some diseases in equine. Alternatively, studies showed vaccination against tetanus elicited a strong acute phase response [ 77 ], and vaccination against WNV changed the serum proteins and leukocyte count profiles [ 78 ]. Further studies should be pursued to investigate the benefit of using the acute phase proteins and cell count as biomarkers to assess the immune response from vaccination.…”
Section: Other Considerationsmentioning
confidence: 99%
“…This highlights that adapting protocols based on titers can be achieved for some diseases in equine. Alternatively, studies showed vaccination against tetanus elicited a strong acute phase response [ 77 ], and vaccination against WNV changed the serum proteins and leukocyte count profiles [ 78 ]. Further studies should be pursued to investigate the benefit of using the acute phase proteins and cell count as biomarkers to assess the immune response from vaccination.…”
Section: Other Considerationsmentioning
confidence: 99%
“…Since 2008 a vaccine constituted by inactivated WNV strain, VM-2, was licensed for use in horses in the EU by the European Medicines Agency (EMA). In this regard, a study carried out in Southern Italy concluded that vaccines used do not alter the overall hemogram picture and health status of horses though it is associated with modulation of humoral immunity, leukocyte populations, and inflammatory markers [ 24 ]. Contrariwise, to date, no vaccine is available for human [ 25 , 26 , 27 , 28 ]: Even though several vaccines targeting flaviviruses (e.g., TBE, yellow fever, Dengue, Japanese encephalitis, and Kyasanur forest disease) have been made available, none has been licensed for the use against WNV infection [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each horse was free from internal and external parasites (regularly treated every three months), regularly subjected to Coggins tests (one time a year), and vaccinated against influenza and tetanus. The annual vaccinations were performed three months prior to the experimental period, and the last one was postponed until the end of the experiment [25,26]. All horses were fed three times a day (6:30, 12:00, and 19:00).…”
Section: Animalsmentioning
confidence: 99%